Resilience theory as a framework in understanding politico-administrative synergy - Oppus, Pamela G. (2009)
As a key agent of stability, order, and sustainability, the bureaucracy in periods of political transition (usually caused by electoral activities) is challenged in terms of efficiency, effectiveness, responsiveness, and continuity of public services and development programs. The bureaucracy is a safety net for change that threads one political term to another. Understanding the bureaucracy using "resilience" theory reconstructs public administration terms such as inefficiency, slavery to politics, partially to leadership personalities, management failure of sustainability strategies, that oftentimes undermine the role, capacity, and strength of its bureaucracy. Resiliency is the capacity for, or the outcome of successful adaptation despite challenging or threatening circumstance.
Keywords: Bureaucracy; Resilience (Psychology)